Chronic Disturbance in a Tropical Dry Forest: Disentangling Direct and Indirect Pathways Behind the Loss of Plant Richness - Jara-Guerrero, Andrea; González-Sánchez, Diego; Escudero, Adrián; Espinosa, Carlos I. (Frontiers in Forests and Global Change, 2021)
Chronic disturbance is widely recognized as one of main triggers of diversity loss in seasonally dry tropical forests. However, the pathways through which diffuse disturbance is acting on the forest are little understood. This information is especially demanded in the case of vanishing Neotropical seasonally dry forests such as the Tumbesian ones. We proposed a conceptual model to analyze the factors behind the loss of woody species richness along a forest disturbance gradient, explicitly considering the existence of direct and indirect causal pathways of biodiversity loss. We hypothesized that the chronic disturbance can act on the woody species richness directly, either by selective extraction of resources or by browsing of palatable species for livestock, or indirectly, by modifying characteristics of the forest structure and productivity. To test our model, we sampled forest remnants in a very extensive area submitted to long standing chronic pressure. Our forests cells (200 x 200 m) were characterized both in terms of woody species composition, structure, and human pressure. Our structural equation models showed that chronic disturbance is driving a loss of species richness. This was done mainly by indirect effects through the reduction of large trees density. We assume that changes in tree density modify the environmental conditions, thus increasing the stress and finally filtering some specific species. The analysis of those pathways, direct and indirect, allows us a better understanding of the processes behind the species loss in this seasonally dry tropical forest.